Analisis finansial usaha budidaya rumput laut berdasarkan uji pertumbuhan bibit dengan dengan jarak ikat berbeda - Gaghaube, Agus; Ngangi, Edwin L.A; Mudeng, Joppy D. Mudeng D (Universitas Sam Ratulangi, 2013)
The purpose of this study was to analyze the financial feasibility of the test Kappaphycus alvarezii seaweed cultivated with different seed tight distance. The study was conducted in Talengen Bay, Tabukan Tengah, Regency of Sangihe Islands from April to May 2013. Seed tight distance as treatment consisted of A = 10 cm, B = 20 cm, and C = 30 cm. Seaweed was cultivated using surface long-line with initial weight of seed per bond was 100 g. Containers measuring 16 x 10 mÂ² were divided into nine small plot of 4 x 2 mÂ² , each with three ris. The trial was conducted for over 42 days, and weighed every 14 days. Results obtained displayed the best growth was achieved at treatment C (distance of 30 cm) followed by distance of 20 cm, and 10 cm. Analysis of total revenue (total profit) found that seedlings 10 cm distance seed tight was the highest, followed by distance 20 cm and 30 cm. Income level analysis results (profit rate) found that 30 cm distance was the highest, followed by distance 10 cm and 20 cm. As conclusion, the cultivation of seaweed K. alvarezzi was financially viable based on 30 cm seed tight distance. Keywords: Kappaphycus alvarezii, total profit, profit rate, Talengen Bay